Analisis Prosedur Dan Administrasi Marketing Pada Dealer Mobil Di Pematangsiantar - Eka Pratiwi Septania Parapat; Debora Silvia Hutagalung; Eve Ida Malau (SEKOLAH TINGGI AKUNTANSI DAN MANAJEMEN INDONESIA (STAMI), 2021)
The purpose of this study was to analyze the marketing administration procedures at Car Dealers in Pematangsiantar. The data collection technique carried out by the author is by observation and interviews. The data collected will be analyzed by the author with a qualitative analysis technique where the author himself is the analysis tool. In the process of this analysis, the authors are still looking for new findings and facts to support the relevant research results. The results of this study are in the form of an analysis of marketing administration that occurs in the company under study. It is hoped that the results of this analysis can be a solution to the problems experienced by the company, especially related to marketing administration.. Keywords: Marketing Administration, Sales Management,